The Effect of Financial and Macroeconomic Performance on Stock Value in Companies in the Restaurant, Hotel and Tourism Sub-Sector Companies Listed on the IDX During the Covid-19 Pandemic - Amalia, Rizky; Arnita, Vina (Journal of Community Research and Service, 2024)
This research aimed to determine the influence of return on equity, earnings per share, debt to equity ratio, inflation, exchange rate, and interest rate both partially and simultaneously on stock value in the Restaurant, Hotel, and Tourism Sub-Sector Companies Listed on the Indonesia Stock Exchange during the Covid-19 Pandemic. The population of this research consisted of 35 companies, with a sample of 26 companies. The analysis technique used panel data regression with the Eviews 9.0 application. The regression model used was the Random Effect Model (REM). The data used were from the first to the fourth quarter of 2020 to 2021 and the first quarter of 2022. The results of the research showed that only the earnings per share variable had a partially positive and significant effect on the stock value of the Restaurant, Hotel, and Tourism Sub-Sector Companies listed on the Indonesia Stock Exchange during the Covid-19 Pandemic. Meanwhile, the variables of return on equity, debt to equity ratio, inflation, exchange rate, and interest rate did not have a significant effect. Simultaneously, all variables of return on equity, earnings per share, debt to equity ratio, inflation, exchange rate, and interest rate had a positive and significant effect on stock prices. The variables of return on equity, earnings per share, debt to equity ratio, inflation, exchange rate, and interest rate contributed only 8.97% to the formation of stock prices and had a weak relationship with stock prices.